Kinerja Multi-user MIMO OFDM dengan Block-Diagonalization Precoding - Puji Handayani; Beny Burhanusshomad (Universitas Darul Ulum, 2023)
Multiple-input multiple-output (MIMO) is a transmission technology that uses more than one antenna both on the transmitter side and on the receiver side. In the communication services, the system will involve more than one active user who uses one base station (BS) together so that it is called multi-user MIMO (MU-MIMO). This paper discusses the performances of MU-MIMO when it uses block diagonalization (BD) precoding and applies minimum mean squared error (MMSE) detector. As a comparison we also apply zero-forcing (ZF) detector. From the simulations that have been done, it is found that the MMSE had better performances than the ZF detector in terms of BER. We also consider the performance when users are moving. The simulation results show that BER performances are decrease slowly when users are moving.